Quality Assurance Management in Enhancing School Quality Using the PPEPP Method at SMK Darul Musthofa Assunniyyah Yosowilangun Lumajang - Kutsiah, Kutsiah; Saihan, Saihan; Usriyah , Lailatul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study examines the implementation of Quality Assurance (QA) Management using the PPEPP method at SMK Darul Musthofa Assunniyyah Yosowilangun Lumajang to enhance school quality. The research employs a qualitative descriptive approach, utilizing interviews, observations, and documentation to gather data from 30 informants, including school principals, teachers, curriculum coordinators, and administrative staff. The study was conducted over three months (January-March 2025). The findings indicate that the PPEPP method has positively impacted the planning and implementation of academic programs, fostering structured management and improving teacher professionalism. However, challenges remain in the evaluation and control phases, particularly in integrating evaluation results into decision-making processes. The lack of digitalization and systematic monitoring mechanisms hinders the effectiveness of QA implementation. Teachers and school administrators recognize the importance of QA but highlight the need for further training and data-driven decision-making. To optimize QA management, the study recommends enhancing digitalization in documentation, strengthening professional development programs for teachers, and integrating technology in quality monitoring. These improvements will ensure that QA is not merely an administrative function but a continuous effort to enhance educational quality. The study contributes valuable insights for school administrators and policymakers in optimizing QA strategies and serves as a reference for future research in educational quality management